A mixed-method evaluation of the relationship between Oxford classification scores and longitudinal changes in proteinuria in patients with immunoglobulin A nephropathy - Xu, Ri-Cong; Guo, Jian-Ying; Cao, Tao; Xu, Yi; Liao, Ying; Chen, Yu-Na; Song, Hai-Ying; Chen, Xiao-Jie; Guan, Mi-Jie; Tang, Fei; Xiang, Qiong; Chen, Xing-Lin; et al. (Frontiers in Endocrinology, 2023)
Introduction This study aimed to investigate the relationship between Oxford Classification scores and longitudinal changes in proteinuria in patients with immunoglobulin A nephropathy (IgAN). Methods The study was a single-center retrospective cohort study involving 358 patients with primary IgAN who were treated at the Shenzhen Second People’s Hospital, China, between January 2011 and May 2021. Multivariate linear regression and generalized additive mixed models (GAMMs), adjusted for traditional risk confounders, were used to evaluate the correlation between scores for mesangial hypercellularity (M), endocapillary hypercellularity (E), segmental glomerulosclerosis (S), tubular atrophy/interstitial fibrosis (T), and crescents (C) (known as the Oxford Classification MEST-C score system), with proteinuria/creatinine ratio (PCR) at the time of renal biopsy and longitudinal changes in PCR, respectively. Results The median PCR was 1061 mg/g, and it increased on average by 68.82 mg/g per year in these patients. Among patients with renal insufficiency, compared with patients without relative lesions, those with E present (E1) (1153.44; 95% confidence interval [CI], 188.99–2117.89 mg/g) and C > 0 (C1/2) (1063.58; 95% CI, 185.25–1941.90 mg/g) were associated with increased PCR levels at the time of renal biopsy. What’s more, S present (S1) (194.96; 95% CI, 54.50–335.43 mg/g per year) was associated with the fastest PCR increase; C > 0 (C1/2) (147.59; 95% CI, 8.32–286.86 mg/g per year) and T >25% (T1/2) (77.04; 95% CI, 7.18–146.89 mg/g per year), were also correlated with a faster PCR increase. In patients with normal kidney function, associations between S1 (55.46; 95% CI, 8.93–101.99 mg/g per year) and E1 (94.02; 95% CI, 21.47–166.58 mg/g per year) and PCR change could be observed. Additionally, in patients with overweight/obesity, S1 (156.09; 95% CI, 52.41–259.77 mg/g per year), E1 (143.34; 95% CI, 35.30–251.38 mg/g per year), T1/2 (116.04; 95% CI, 22.58–209.51 mg/g per year), as well as C1/2 (134.03; 95% CI, 41.73–226.32 mg/g per year) were associated with noticeably quicker PCR increase. Conclusions Overall, E1 and C1/2 were independently associated with raised proteinuria levels at the time of renal biopsy, and S1, E1, T1/2, C1/2 were independently associated with a longitudinal increase in proteinuria in the patients with IgAN, especially in those with renal insufficiency or overweight/obesity, suggesting that currently available treatments might not be satisfactory, and weight control might be beneficial. Individual therapy development might benefit from the use of the Oxford Classification system.